REFLUXO GASTROESOFAGICO E SINTOMAS OTORRINOLARINGOLOGICOS - Bretan, Onivaldo [UNESP]; Henry, Maria Aparecida Coelho de Arruda [UNESP] (My University, 1995)
Gastroesophageal reflux and other gastroesophageal diseases produce symptoms in head and neck region leading individuals to search for ear nose and throat consultation. Otolaryngologist may incorporate investigation of reflux in your daily practice. Comments of gastroesophageal reflux and head and neck complaints are done. To illustrate handling of patients suspected of reflux authors relates a case of a dysphagia patient. Close relationship between otolaryngologist and gastroenterologist in reflux investigation is emphasized.
Gastroesophageal reflux and ear nose and throat complaints
Keywords: gastroesophageal reflux; otolaryngology-investigation; case report; dysphagia; human